A Lagrangian–Eulerian shell–fluid coupling algorithm based on level sets - Cirak, Fehmi; Radovitzky, Raúl (Computers & structures, 2005)
We propose a robust computational method for the coupled simulation of a compressible high-speed flow interacting with a highly flexible thin-shell structure. A standard Eulerian finite volume formulation on a fixed Cartesian mesh is used for the fluid, and a Lagrangian formulation based on subdivision finite elements on an unstructured mesh is used for the shell. The fluid–shell interface on the Cartesian mesh is tracked with level sets. The conservation laws at the interface are enforced by applying proper interface boundary conditions to the fluid and shell solvers at the beginning of each time step. The basic approach furnishes a general algorithm for explicit loose coupling of Lagrangian shell solvers with Cartesian grid-based Eulerian fluid solvers. The efficiency and robustness of the proposed approach is demonstrated with an airbag deployment simulation.